ASSESSMENT OF PRIMARY PRODUCTIVITY AND CHLOROPHYLL-a IN RELATION TO HYDROLOGICAL CHARACTERISTICS OF CHILIKA LAGOON - PARIDA, SAIBALA; BHATTA, KRUPA SINDHU; ROUTRAY, RAJESH KUMAR; PATTNAIK, AJIT KUMAR (Journal of the Inland Fisheries Society of India, 2021)
The study deals with the assessment of phytoplankton primary productivity and chlorophyll-a in relation to hydrological features in Chilka lagoon during September 2007 to March 2008. A qualitative evaluation of some physico-chemical and biological parameters has been carried out in order to verify association among primary productivity, community respiration and chlorophyll-a with water quality parameters. Statistical analysis i.e., regression analysis and principal component analysis were used to establish hydro-biological relationships between different components. Key words: Primary productivity, chlorophyll-a, water quality, Chilika Lagoon